Hemoptysis after subclavian vein puncture for pacemaker implantation: A case report - Bagchi, Avishek; Agarwal, Rajendra Kumar; Talwar, Kewa Kishan (Journal of Cardiology and Cardiovascular Medicine, 2019)
Background: Subclavian venous access for pacemaker lead insertion is a common procedure and is normally considered safe in the hands of an expert. However, subclavian venepuncture is not without complications, starting from mild subcutaneous hematoma to pneumothorax. We here present a case of hemoptysis occurring after difficult subclavian vein puncture, which subsequently improved on conservative management only. Case Summary: A 65-year-old gentleman, post aortic valve replacement had persistent high-grade AV block and was taken up for a dual chamber pacemaker implantation. Immediately following venous access, he had a bout of hemoptysis, which recovered on its own. Post procedure chest x-ray was suggestive of alveolar hemorrhage which cleared gradually in next three-four days. Discussion: Post subclavian venepuncture hemoptysis is known; but it is a rare complication, arising either because of lung parenchyma injury or arterial injury. This is mostly benign and improves on conservative management only; however rarely it may be massive and life threatening where transcatheter arterial embolization may be required.